Preparation and In Vitro Permeation of Chlopheniramine Maleate (CPM) from Gel through Rat Skin - Balkis A. Kamal; Wissam S. Mahmood (College of Pharmacy University of Baghdad, 2017)
Chlopheniramine maleate ( CPM ) , is  one  of   the  H- receptor antagonist  ,  widely used  in allergic  diseases ,like skin rash  and  pruritis .CPM 3%w/w was successfully  loaded in  2%w/w  sodium alginate (SA)    as a gel    base ,  and  to be considered   as  a  selected  formula .It was found  that  the diffusion   of  CPM    through   the  skin  of  albino  rat   was     increased   as  the concentration  of  CPM  increased from 2 %w/w sodium alginate  ,  More over , the  addition of Triethanolamine  5 % w/w,  to  sodium  alginate   2 % w/w  , loaded by  CPM 3 % w/w , enhanced the amount   of     CPM  diffuse through the skin  of albino rat . Mean while the addition  of  PEG 1000 2% w/w  , and urea 5 % w/w, separately  to       sodium alginate 2 % w/w , loaded by  CPM 3 % w/w , hindered  significantly  P<0.05 the  amount  of the drug diffused  through the skin of the rat .The  selected  formula of sodium alginate  2% w/w as a base loaded by CPM 3% w/w was  physically  acceptable , with shelf life approximately  3.3  years .  Key wards:  chlopheniramine maleate , gel , skin permeation